REKONSTRUKSI BAHAN AJAR SINTESIS SENYAWA ANORGANIK UNTUK MAHASISWA CALON GURU KIMIA MENGGUNAKAN MODEL OF EDUCATIONAL RECONSTRUCTION - yenni kurniawati (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2018)
AbstractBilions of new inorganic compounds and many synthetic methods has discovered for decades based on many reason. Its wider use makes inorganic compounds continuously synthesized by chemists. However, most of them were not produced in Indonesia. One of the solution was preparing synthesizing inorganic compounds subject matter to preservice chemistry teacher. Nevertheless, because it is not easy to mastered, didactic reduction must be done. The objection of this study was to reconstructed this subject matter using the Model of Educational Reconstruction (MER), start form curriculum analysis, empirical studies, and analysis of content structure. This research was conducted by mixed method exploratory design, with preservice chemistry teacher 6th and 8th semester as the sample. The reconstruction of synthesis inorganic compounds subject matter material was the following sequence of macro propositions: general description of synthesized of inorganic compounds, benefits of the inorganic compounds, reactions that can underlie possible formation of inorganic compounds, the thermodynamics and kinetics of reactions processes the properties of the inorganic compounds, basic synthesis techniques and basic characterization techniques. And the most important thing that must be understood by potential chemists are: material characteristics, molecular structure of compounds, and chemical reaction.Keywords : Model of Educational Reconstruction, synthesis of inorganic compounds, preservice chemistry teacher